Hepp bounds of phi^4 graphs with <=11 loops - Panzer, E (University of Oxford, 2022)
This text is human readable and also compatible with the MAPLE computer algebra system. It contains the values of the Hepp bound (the volume of the polar of the spanning tree polytope) of graphs that arise from 4-regular graphs after deleting a vertex. The data was computed with a MAPLE program on 27 May 2016. For more information, see the comments at the beginning of the file.